Clinical manifestation of mitochondrial diseases - Magner, Martin; Kolářová, Hana; Honzík, Tomáš; Švandová, Ivana; Zeman, Jiří (Developmental period medicine, 2015)
Mitochondrial disorders (MD) represent a clinically, biochemically and genetically heterogeneous group of diseases associated with dysfunction of the oxidative phosphorylation system and pyruvate dehydrogenase complex. Our aim was to illustrate the most common clinical presentation of MD on the example of selected diseases and syndromes. The minimal prevalence of MD is estimated as 1 to 5,000. MD may manifest at any age since birth until late-adulthood with acute manifestation or as a chronic progressive disease. Virtually any organ may be impaired, but the organs with the highest energetic demands are most frequently involved, including brain, muscle, heart and liver. Some MD may manifest as a characteristic cluster of clinical features (e.g. MELAS syndrome, Kearns-Sayre syndrome). Diagnostics includes detailed history, the comprehensive clinical examination, results of specialized examinations (especially cardiology, visual fundus examination, brain imaging, EMG), laboratory testing of body fluids (lactate, aminoacids, organic acids), and analysis of bioptic samples of muscle, skin, and liver, eventually. Normal lactate level in blood does not exclude the possibility of MD. Although the aimed molecular genetic analyses may be indicated in some of mitochondrial diseases, the methods of next generation sequencing come into focus. Examples of treatment are arginine supplementation in MELAS syndrome, ketogenic diet in pyruvate oxidation disorders or quinone analogs in patients with LHON. Conclusion: The clinical suspicion of a mitochondrial disorder is often delayed, or the disease remains undiagnosed. The correct diagnosis and adequate treatment can improve prognosis of the patient. Access to genetic counseling is also of great importance.
Keywords: Kearnsův-Sayreův syndrom; Mitochondrial Encephalomyopathies; MELAS Syndrome; mitochondriální nemoci; DNA, Mitochondrial; lidé; Mitochondrial Myopathies; mitochondriální encefalomyopatie; Mitochondrial Diseases; mozek; mitochondriální myopatie; Brain; mitochondriální DNA; Kearns-Sayre Syndrome; MERRF Syndrome; elektroencefalografie; syndrom MELAS; syndrom MERRF; Electroencephalography; Humans